Virtual commissioning for an Overhead Hoist Transporter in a semiconductor FAB - Lee, Joo Y.; Lee, Kwanwoo; Park, Sangchul (International Journal of Production Research, 2020)
Presented in the paper is a virtual commissioning methodology for the design and verification of an OHT (Overhead Hoist Transporter), which is a vehicle that travels on the overhead track in a FAB (Factory for making semiconductor chips), and directly accesses the load port of the stocker or process equipment by the belt driven hoisting mechanism. Since the material flows of a FAB is extremely complicated, it is important to design the OHT control software by considering various situations. The proposed virtual commissioning methodology supports the full verification of the OHT control software by performing the simulation involving a ‘virtual OHT model’ and a ‘real OHT controller’. We separate the virtual OHT model into two parts, a physical model (mechanical part) and a logical model (electrical part) to achieve the concurrency of mechanical and electrical designs of an OHT. Virtual commissioning identifies and addresses design flaws and operational faults so that significant savings can be achieved. The prototype of the proposed virtual commissioning methodology has been implemented and tested with several examples.
Keywords: Control software; HILS; Hoisting mechanism; Mechanical and electrical; Process equipments; Semiconductor chips; Semiconductor fabs; Virtual commissioning; control software verification; HILS; OHT; virtual commissioning